A Critical Review on Balachaturbhadra Churna: An Effective Ayurveda Formulation for the Pediatric Age - Abhishek Joshi; Shrikrishna Rajagopala; Patel Kalpana S. (International Journal of Interreligious and Intercultural Studies, 2019)
Balachaturbhadra Churna offers a multitude of health benefits for which it has become so poapular prescription by Kaumarbhritya practioners of Ayurveda. It is a combination of four drugs Musta, Pippali, Ativisha and Karkatashringi. This combination was first mentioned in Chakradatta and has been in practice since a millennium. Many queries have been raised on the usage of Aconite species of drugs recently, thus doubting the safety and efficacy of Balachaturbhadra Churna. Very few works have been published on Balachaturbhadra Churna till now. The aim of the present study was to compile and review such available references from classics and research works published on Balachaturbhadra Churna. Total five studies are published on Balachaturbhadra Churna, which revalidated the impact of classical guidelines. The research papers revealed standards of Quality Control and pharmacological efficacy of the drug. All the experimental studies revealed that Balachaturbhadra Churna is having no toxic hazards at very higher Dose levels, proving it safe for therapeutic use. Though certain limitations were observed in these researches, the results can be considered as a lead for further well stratified clinical studies.